EVALUASI PENYELENGARAAN PROGRAM KELAS MODEL DI SMA N 1 SUKADANA KABUPATEN KAYONG UTARA - Irvan, Muhammad; Amin, Maswardi Muhammad; Syukri, Muhammad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe focus of this research is the evaluation of the implementation of a model class program in SMA Negeri 1 Sukadana, North Kayong Regency. Types of qualitative evaluation research. To collect data and information from informants, researchers used interviews, observations and study documents. The subject of the study was the Head of the North Kayong District Education Office, the Principal of SMA N 1 Sukadana, the teacher who taught the class model, the manager, the head of the dormitory and the students of the model class program at SMA Negeri 1 Sukadana. The conclusion of this study is that the legal basis for implementing the model class program is the regent's regulation no. 12 of 2017 concerning the program class model, the technical guidelines for the model class program and the laws relating to the program class model. For the recruitment process of students and educators is sufficient, as well as the selection process, teaching and learning activities and the development of model class programs have also been running quite well. Furthermore, the results of the national exams show that students taking the class program get high category scores, but it is unfortunate that there are still students who do not continue their education to higher education or become TNI Polri.Keywords: Evaluation, Organizing Model Class Program